Narsisme Ulama: Dilema dan Posibilitas Rekonstruksi Ushul Fiqh di Indonesia - Adelina Nasution (Al-Ahkam, 2018)
This paper  describe the construction of the uṣūl al-fiqh  initiated by Hasan al-Turabi that be dialogued with the religious conditions in Indonesia. Its aim is to find the possibility and inventory the constraints of the reconstruction of the uṣūl al-fiqh in Indonesia. This study uses the hermeneutical method of Paul Ricoeur in analyzing the theoretical ideas of Hasan al-Turabi. In this study found the biggest dilemma of reconstruction of uṣūl al-fiqh in Indonesia: the narcissism of scholars and egoism of intellectuals. Apart from that, there are conditional possibilities found, in order to reconstruct uṣūl al-fiqh  in Indonesia, i.e.: 1) willingness, facilities, protection and consistency of the government, and 2) the inclusiveness of traditional clerics in order to create a dialogue on the traditional jurisprudence understood by them with the modern scholars and experts of various sciences. The author concluded that only the integration of modern sciences with the traditional Islamic jurisprudence, that uṣūl al-fiqh reconstruction could be implemented in Indonesia.